Graywater Reuse: The Effects on Income and Agricultural Production Sustainability of Family Farming Systems in the Semiarid Region of Ceará, Brazil - Silva, Maria Josiell Nascimento da; Khan, Ahmad Saeed; Lima, Patrícia Verônica Pinheiro Sales (Journal of Agricultural Studies, 2021)
The semi-arid region of Ceará is a Brazilian area that is exposed to long and frequent periods of drought. Water scarcity is a threat to the population’s well-being and agricultural activities. We evaluated the effects of graywater reuse for agriculture on income and sustainability of agricultural production in the municipality of Iguatu, located in the semiarid region of the state of Ceará. It is an important research because it deals with a strategy that aims to reduce farmers’ vulnerability to the lack of water. There are no studies that assess the impacts of water reuse in the region. The propensity score matching technique was applied, and primary data were obtained by interviewing beneficiaries (treated group) and non-beneficiaries (control group). The results showed that the program has effects on sustainable agricultural production of small farmers because of the use of non-aggressive agricultural practices. In the group of beneficiaries, the income is 21.9% higher than of that in the group of non-beneficiaries. In addition, families that adopt water reuse have 26.8% higher levels of sustainability than those that do not adopt this strategy of living with drought.